Physical Activity as a Modulator of Gut Microbiota Diversity: Evidence from Human Studies - Kossakowska, Julia; Ruszkowski, Marcin; Celmer, Mikołaj; Majchrzak, Mateusz; Kacprzak, Urszula; Biernacka, Zofia; Piątkowski, Norbert; de Laval, Andrzej (Quality in Sport, 2026)
Introduction and purpose: The human gut microbiota plays a crucial role in maintaining overall health, influencing metabolic, immune, and neurological processes. Physical activity has emerged as a potentially modifiable factor affecting gut microbiota composition and diversity. The aim of this narrative review was to evaluate current evidence on the impact of physical activity on gut microbiota diversity in humans. Brief description of the state of knowledge: This review was based on a comprehensive search of PubMed and Google Scholar and included studies published between 2010 and 2026. Only studies involving human participants and examining the relationship between physical activity and gut microbiota were considered. Available evidence indicates that physical activity is associated with changes in gut microbiota composition and, in some cases, with increased diversity and a greater abundance of beneficial bacterial taxa. Both observational and interventional studies suggest that exercise may positively influence microbial composition; however, the magnitude of these effects depends on exercise type, intensity, duration, and individual characteristics. Diet was consistently identified as a major confounding factor influencing gut microbiota outcomes. Summary: Physical activity appears to be an important modulator of gut microbiota in humans, with more consistent effects on microbial composition and function than on overall diversity. However, these effects are complex and influenced by multiple interacting factors, particularly dietary habits. Further well-designed human studies are needed to clarify the mechanisms underlying these interactions.